Grammatical and sociolinguistic aspects of Ethiopian languages - Derib Ado; Gelagay, Almaz Wasse; Johannessen, Janne Bondi 1960- (John Benjamins Publishing Company, 2021)
"The focus of this unique publication is on Ethiopian languages and linguistics. Not only major languages such as Amharic and Oromo receive attention, also lesser studied ones like Sezo and Nuer are dealt with. The Gurage languages that often present a descriptive and sociolinguistic puzzle to researchers receive ample coverage. And for the first time in the history of Ethiopian linguistics two chapters are dedicated to descriptive studies of Ethiopian Sign Language, as well as two studies on acoustic phonetics. Topics range over a wide spectrum of issues covering the lexicon, sociolinguistics, socio-cultural aspects and micro-linguistic studies on the phonology, morphology and syntax of Ethiopian languages"
Keywords: Äthiosemitische Sprachen; Soziolinguistik; Grammatik; Ethiopian languages / Grammar; Ethiopian languages / Social aspects; Aufsatzsammlung